Analisis Faktor-Faktor yang Mempengaruhi Capaian Pembelajaran Mahasiswa Selama Perkuliahan Daring di Masa Pandemi Covid-19 - Muhamad Rovi; Ahmad Raf'ie Pratama; Taufik Hidayat (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The COVID-19 pandemic that has hit the entire world, including in Indonesia, has had an impact on all aspects of life, one of which is higher education. The COVID-19 pandemic is forcing students to do online learning in full. Although the era of globalization with advanced information technologies has provided convenience in terms of exchanging information, which is the substance of online learning process, there are still many problems, both technical and non-technical ones. This study aims to explore what factors can hinder the effectiveness of online learning that in turn can affect learning achievement in a negative way, especially in the context of the COVID-19 pandemic from Indonesian perspective. The data for this study was collected through a survey of 150 university students in Indonesia and analyzed using the structural equation modeling (SEM) method. The results showed that time zone differences were the most inhibiting factor for online learning, followed by the lack of technical expertise and information technology infrastructure. The results of this study can provide a better picture for policy makers in Indonesian higher education systems, both during this COVID-19 pandemic, and in the future, including in the implementation of distance education that also relies heavily on online learning activities.